An Update in the Use of Antibodies to Treat Glioblastoma Multiforme. (5th November 2013) - Hernández-Pedro, Norma Y.; Rangel-López, Edgar; Vargas Félix, Gustavo; Pineda, Benjamín; Sotelo, Julio
Abstract : Glioblastoma is a deadly brain disease and modest improvement in survival has been made. At initial diagnosis, treatment consists of maximum safe surgical resection, followed by temozolomide and chemoirradiation or adjuvant temozolomide alone. However, these treatments do not improve the prognosis and survival of patients. New treatment strategies are being sought according to the biology of tumors. The epidermal growth factor receptor has been considered as the hallmark in glioma tumors; thereby, some antibodies have been designed to bind to this receptor and block the downstream signaling pathways. Also, it is known that vascularization plays an important role in supplying new vessels to the tumor; therefore, new therapy has been guided to inhibit angiogenic growth factors in order to limit tumor growth. An innovative strategy in the treatment of glial tumors is the use of toxins produced by bacteria, which may be coupled to specific carrier-ligands and used for tumoral targeting. These carrier-ligands provide tumor-selective properties by the recognition of a cell-surface receptor on the tumor cells and promote their binding of the toxin-carrier complex prior to entry into the cell. Here, we reviewed some strategies to improve the management and treatment of glioblastoma and focused on the use of antibodies.